A comparison between microalgae virtual biorefinery arrangements for bio-oil production based on lab-scale results. (1st September 2016) - Silva, C.M.; Ferreira, A.F.; Dias, A.P.; Costa, M.
Abstract: Bio-oils are typically produced by pyrolysis processes. Bio-oils can be used directly in a generator to produce electricity or upgraded to produce transportation fuels. Nowadays the interest is that they come out in a biorefinery context. This paper compares bio-oil production within three possible procedures. Targeting the bio-oil product, in virtual biorefinery #1, microalgae is processed by solvent ultrasound-assisted extraction, and lipids follow transesterification; in virtual biorefinery #2, bio-oil comes out from fresh microalgae pyrolysis, and, finally, in virtual biorefinery #3, lipid extraction leftovers proceed for slow pyrolysis. Solvent ultrasound-assisted extraction and slow pyrolysis are tested and measured experimentally using three microalgae as feedstock: Chlorella vulgaris, Nannochloropsis oculata, and Scenedesmus obliquus . These stand-alone processes are analyzed aiming to provide the best option in a virtual biorefinery context. Although very fast/slow pyrolysis produces markedly different products, previous thermogravimetry analysis allowed choosing an adequate pyrolysis temperature. Nevertheless, the influence of temperature, catalyst and nitrogen flow is depicted. The comparison indicators for final remarks relate to final energy consumption and greenhouse gas emissions. Conditions that favor bio-oil production may not be favorable in terms of energy required per mass or energy output. If mass allocation criterion is used lipid extraction followed by slow pyrolysis of the leftovers is advantageous over slow pyrolysis of fresh dry microalgae. Still the fossil energy input largely surpasses the bio-oil energy content. Graphical abstract: Highlights: Ultrasound assisted solvent lipid extraction (LE) spends 146–148 MJ/kgdry microalgae . Bio-oil depends on pyrolysis temperature, N2 flow and catalyst, maximum 58.1 wt%. LE, transesterification and pyrolysis as a favorable carbon footprint. 21.6 MJfossil/MJbio-oil implies process optimization and renewables increase needs. System expansion and mass allocation criteria give the same ranks.